Everyday-life: "the fourth social dimension? - Oliva, Jaime Tadeu (GEOUSP Espaço e Tempo (Online), 1997)
By comparing some of Henri Lefebvre's and Juergen Haberma s reflections, this article points out the emergence of the concepts of everyday life and "lived world" in the philosophical field and on human sciences (specially in Geography). It also verifies that the conceptions of current truth go under change and amplification including the role of aesthetics as the insertion of everyday life (and/or "lived world") in social studies reveals the existence of differences and other rationalities which are despised by the conventional practice of sciences and philosophy